Early in-session predictors of response to trauma-focused cognitive therapy for posttraumatic stress disorder - Ehlers, A; Warnock-Parkes, E; Brady, F; Barker, C (Elsevier, 2015)
Trauma-focused cognitive behaviour therapy is effective in treating posttraumatic stress disorder but non-response rates range between 25% and 50%. Results of previous research on patient characteristics predicting outcome are inconsistent and mainly focused on demographic and diagnostic variables. This study examined whether behavioural predictors of poor treatment response can be observed in early sessions. It was predicted that greater patient perseveration, lower expression of thoughts and feelings and weaker therapeutic alliance would be associated with poorer outcomes. We also explored the relationships of patient behaviours with therapeutic alliance and the efficiency and competence of treatment delivery. Audio or video recordings of the initial treatment sessions of 58 patients who had shown either good (n = 34) or poor response (n = 24) to cognitive therapy for PTSD (CT-PTSD, Ehlers and Clark, 2000) were blindly coded for patient perseveration, expression of thoughts and feelings, therapeutic alliance, efficiency and competency of treatment delivery and therapist competence. Poor responders showed more perseveration and less expression of thoughts and feelings in the initial session. Patient perseveration and low expression of thoughts and feelings were associated with poorer therapeutic alliance and compromised treatment delivery. Patients with these behavioural characteristics may benefit from additional treatment strategies. Limitations of the study and implications for clinical practice are discussed.